CLASSE, GÊNERO, RAÇA E MOVIMENTOS SOCIAIS: a luta pela emancipação - Helena Hirat (Revista de Políticas Públicas, 2018)
The present article results of a theoretical research on women participation on labor, highlighting the male dominance and exploit issue through history, despite the great economical, social, and legal changes occured in those fields. Accentuate, among the presence of occupational men “ghettos”, in areas like civil construction, aviation and mining, while there are few men, for example,in nursery, housework and among caregivers. Concludes that two relevant ways are adopted simultaneously by industrialized societies to overcome the difficulties: the path of public policies and the path of action of feminist movements. The common axis is the ethical perspective that inequality is social injustice.